Evaluating the Impact of Information Education and Communication Package on Knowledge and Attitude Regarding Reproductive and Sexual Health among Late Adolescent Girls in Selected Colleges at Madurai - P. Ememal; Shanthi P. (International Journal of Evidence Based Nursing And Practices, 2024)
A quasi-experimental study was carried out to assess the effectiveness of an Information, Education, and Communication (IEC) package on the knowledge and attitudes related to reproductive and sexual health among late adolescent girls attending colleges in Madurai. The study aimed to: assess the changes in knowledge and attitudes before and after the intervention in both control and experimental groups, evaluate the effectiveness of the IEC package, investigate the correlation between knowledge and attitudes, and examine the relationship between pretest levels of knowledge and attitudes with selected demographic variables. The study was based on Ludwig Von Bertalanffy’s General Systems Theory (1968). It utilized a quasi-experimental pre-test post-test control group design, and included 60 late adolescent girls from chosen colleges in Madurai. The data was collected by purposive sampling technique through a self-administered MCQ questionnaire on to assess knowledge and modified five point Likert’s scale to assess attitude among late adolescent girls. Findings: In experimental group, in pertest 22(73.3%) of them had inadequate knowledge, 6(20%) of them had moderate knowledge and 2(6.7%) of them had adequate knowledge. In post-test none of them had inadequate knowledge, 2(6.7%) of them had moderate knowledge and 28(93.3%) of them had adequate knowledge. In experimental group, in pretest 1(3.3%) of them had low attitude, 29(96.7%) had moderate attitude, none of them had high attitude. In the post-test, none of the participants exhibited a low attitude, with 13 (43.3%) demonstrating a moderate attitude and 17 (56.7%) showing a high attitude. A positive correlation was observed between knowledge and attitude in relation to the father's education, religion, residential area, and previous sources of information. In conclusion, the study found a significant difference between the control and experimental groups, and there was a notable improvement in knowledge levels from the pre-test to the post-test within the experimental group. Hence, it is clearly proves that the Information Education Communication package is effective regarding reproductive and sexual health also highly significant need for teaching among adolescent girls for their lifestyle modifications in Colleges.
Keywords: Information Education Communication Package; Knowledge; Late Adolescent Girls; Life Style Modifications; Sexual health; attitude; reproductive health